2021
DOI: 10.1186/s12989-021-00416-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-soluble components of atmospheric particulates from rare earth mining areas in China on lung cancer cell cycle

Abstract: Background This study aims to investigate the effects of water soluble particulate matter (WSPM) on the viability and protein expression profile of human lung adenocarcinoma cell A549 in the Bayou Obo rare earth mining area, and explore the influence of WSPM on the A549 cell cycle. Results It was found that WSPM can inhibit the viability of A549 cells and induce cell arrest in the G2/M phase. Compared with controls, exposure to WSPM10 and WSPM2.5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These finding indicates that RPL18A is lynchpin for the radioprotective effect of MLT. Studies have shown that inhibition of RPL18A expression leads to cell cycle arrest in lung cancer 43 and inhibits the proliferation of mesothelioma cells 44 . In addition, RPL18A could serve as a potential biomarker for clear cell renal cell carcinoma 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These finding indicates that RPL18A is lynchpin for the radioprotective effect of MLT. Studies have shown that inhibition of RPL18A expression leads to cell cycle arrest in lung cancer 43 and inhibits the proliferation of mesothelioma cells 44 . In addition, RPL18A could serve as a potential biomarker for clear cell renal cell carcinoma 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RP deficiency alters the expression of eight major functional genes, including the cell cycle, cell metabolism, signal transduction, and development [21]. For example, inhibition of RPL13 expression by siRNA in A549 cells can block the cell cycle in the G1 phase, thereby influencing the expression level of CDK2, Cyclin D1, E2F1, p21, and RB1 [22]. When RPL32 is silenced, RPL5 and RPL11 translocate from the nucleolus to the nucleoplasm through ribosomal stress, where they bind to murine double minute 2 and block it from binding to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is a benign disease, but it has the ability to invade and maintain the survival function of ectopic tissue, similar to cancer. RPL18A is involved in the cycle arrest process of non-small cell lung cancer A549 cells by affecting the expression of several cell cycle-related proteins, including Cyclin A2 and Cyclin B1 ( 34 ). The expression of GNB2L1 was higher in ectopic endometrial tissue from patients with endometriosis than in normal patients, regardless of whether they were in the proliferative or secretory phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%